Peningkatan Kapasitas Pelaku UMKM melalui Digitalisasi Pencatatan Keuangan Berbasis SAK EMKM pada UMKM Pasadana - Deden Mastaka Ekapraja; Hari Imbrani; Dina Yulia Wijaya; Yuyus Hidayat; Indri Yani (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
This community service activity aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in preparing financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) through the digitalization of financial recording in UMKM Pasadana. The main problems faced by the partners include low accounting literacy, unstructured and simple financial recording practices, and the limited utilization of digital technology in financial management. The implementation method adopts a participatory approach consisting of several stages, namely socialization, training, mentoring, and evaluation. The training focuses on understanding the basic concepts of SAK EMKM and the practical use of simple and applicable digital financial recording applications. Mentoring is conducted directly to ensure that MSME actors are able to implement financial recording independently and sustainably. The results of the activity indicate an improvement in the knowledge and skills of MSME actors in conducting systematic financial recording in accordance with SAK EMKM principles. In addition, MSME actors begin to adopt digital technology in recording transactions, which improves efficiency, accuracy, and transparency of financial statements. This activity also encourages a shift in mindset, where financial recording is no longer viewed as merely administrative, but as a basis for business decision-making. Thus, this community service activity provides a practical contribution to improving the quality of MSME financial management through the integration of accounting literacy and sustainable digital technology utilization.